Effects of Particulate Matter Emissions of Diesel Engine using Diesel–Methanol Blends - A.F. Yusop; R. Mamat; M.H. Mat Yasin; Obeed M. Ali (Journal of Mechanical Engineering and Sciences, 2014)
In this work, palm methyl ester (PME) was added to methanol–biodiesel fuel in order to reduce the emissions. For diesel engines, alcohols are receiving increasing attention because they are oxygenated and renewable fuels. Therefore, in this study, the effect of the PM emission level of a four-cylinder, naturally aspirated, indirect injection diesel engine has been experimentally investigated by using methanol-blended diesel fuel from 0% to 20% with an increment of 5%. The effects of methanol on particulate matter (Laurens, Koolwijk, & De Maat) components, soluble organic fraction (SOF) and dry soot (DS) using different types of fuel blend were investigated. Using a composite filter, the ester–methanol–diesel characteristics such as mass concentration in terms of PM, SOF and DS were analyzed under different engine operating conditions. The results show that the combination of 10% of methanol with 20% of palm methyl ester produces lower PM emissions. It is shown that PME20M10 of methanol–biodiesel fuel can reduce the PM emissions effectively for all load conditions.